(untitled) (Health Renaissance, 2011)
Background: Nerve conduction study (NCS) assesses peripheral nerve functions and has clinical implication. Objective: To study effect of gender on NCS variables in healthy adults. Settings and Design: Department of Physiology, B.P. Koirala Institute of Health Sciences, Dharan, Nepal. Material and Method: The study was done in 34 (m=19, 32±11 years; f=15, 32±12 years) consenting healthy adults. The compound muscle action potential (CMAP) and sensory nerve action potential (SNAP) were recorded. Statistical analysis: The effect of gender on NCS variables was analyzed using Mann Whitney U test. Results: Male vs. female: males had increased CMAP and F-wave latencies (ms) in all tested motor nerves. CMAP duration (ms) was longer in males (p<0.05) in all tested motor nerves: right median (5.9±1.3 vs. 4.92±0.65), left median (5.54±0.91 vs. 4.72±0.57), right ulnar (5.55±1.01 vs. 4.56±0.59), left ulnar (5.71±0.97 vs. 4.64±0.51), right tibial (6.58±0.95 vs. 5.95±0.71), and left tibial (6.98±1.31 vs. 6.21±0.78). Females showed higher sural SNAP amplitude (µV) (23.26±9.23 vs. 15.94±8.42). SNAP duration (ms) was longer in males: right ulnar (1.16±0.19 vs. 1.03±0.06). SNAP latencies (ms) were also longer in males: right sural (2.61±0.44 vs. 2.21±0.36). Males had greater height (165.9±4.74 vs. 149.3±7.24) and weight (60.4±7.2 vs. 53±7.2). Conclusion: Gender has definite effects on NCS variables. Males had higher CMAP amplitude, longer latencies and duration. SNAP latencies and duration were longer in males whereas amplitude was higher in females. Without adjustment for these factors, the sensitivity and specificity of NCS will decrease when using the same reference data in patients with different gender. Keywords: compound muscle action potential; gender; nerve conduction study; sensory nerve action potential DOI: 10.3126/hren.v8i3.4210 Health Renaissance, September-December 2010; Vol 8 (No.3);169-175